Validation of a computer-based colonoscopy simulator - Sedlack, Robert E.; Kolars, Joseph C. (Gastrointestinal endoscopy, 2003)
Background The computer-based colonoscopy simulator is intended to provide a realistic colonoscopic experience and feedback to operators regarding procedure skills. Advocates hope that computer-based colonoscopy simulators will enhance the mastery of colonoscopy by trainees. Before this hypothesis can be tested, the calims made for a simulator must be validated. The aims of this study were to answer the following: Does a computer-based colonoscopy simulator provide a “realistic” experience? Do computer-based colonoscopy simulators' performance parameters differentiate varying levels of experience? Methods: Ten staff gastroenterologists, 6 gastroenterology fellows, and 6 residents each performed 2 computer-based colonoscopy simulator colonoscopies and performance parameters were recorded. Staff colonoscopists then completed a 6-item survey grading the “realism” of the simulation and procedure difficulty. Survey responses and performance scores were compared with the Wilcoxon rank-sum test. Results: Faculty found the computer-based colonoscopy simulator experience to be realistic despite the “cases” being markedly easier than actual colonoscopy. The computer-based colonoscopy simulator distinguishes subjects according to endoscopic experience with 3 of its measured parameters (total procedure time, insertion time, time in “red-out”). No significant difference in the ability to distinguish among user types was found for the other 10 computer-based colonoscopy simulator measurements for which data were analyzable. Conclusion: The computer-based colonoscopy simulator provides a favorable degree of virtual realism with regard to visual simulation and colonoscope mechanics, although the “cases” were regarded as considerably easier than actual colonoscopy. The computer-based colonoscopy simulator has only limited capability for distinguishing varying levels of competence at actual colonoscopy. These findings suggest that a study to determine the role of computer-based colonoscopy simulators in the curriculum of trainees is warranted. (Gastrointest Endosc 2003;57:214-8.)